'God Has Wrapped Himself in a Cloak of Materialism': Marxism and Jewish Religious Thought in the Early Soviet Union - Slater, Isaac (Religions, 2023)
Jewish religious life in the Soviet Union is typically the subject of dichotomous depictions that offer only a superficial rendering of this rich and complex environment. This paper aims to complicate this image by pointing out several religious thinkers who engaged with Communist and Marxist ideas and incorporated them into their religious thought, while upholding rabbinic culture. Among the figures and themes examined are Alter Hilewitz’s (1906–1994) Hasido-Marxism, Rabbi Avraham Yosef Guttman’s (1870–1940) crisis of faith, and Shmuel Alexandrov’s (1865–1941) use of Russian Nietzscheanism. Alexandrov was also the narrator who revealed these fascinating ideas to us in a rare collection of his letters, which possesses both a philosophical and a theological nature. These letters, which have received very little attention in previous studies, provide a small window into the conflictual world of rabbis and yeshiva students in the first decade of the Soviet Union. Reviewing the ideas generated in a struggle to make sense of one of the great crises of modern Judaism, and pondering questions of historical perspective and how empathy may distort it, this article wishes to go beyond the image of a defensive preservation of religious life and to re-envision this unique and innovative period of Jewish thought.